2001
DOI: 10.1016/s0893-133x(00)00178-0
|View full text |Cite
|
Sign up to set email alerts
|

Low versus Standard Dose mCPP Challenge in Obsessive-Compulsive Patients

Abstract: In several reports, the acute oral administration of the partial serotonergic agonist meta-chlorophenylpiperazine (mCPP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Activity in this procedure is unrelated to an influence upon anxiety (benzodiazepines are inactive at non-sedative doses), but a possible relationship to compulsive behavior should be evoked, as SSRIs and clomipramine, which are potently active in this procedure (Millan et al 2001;Brocco et al 2006;Nicolas et al 2006), are clinically used for the treatment of obsessive-compulsive disorders (Erzegovesi et al 2001;Micallef and Blin 2001;Millan 2006). However, 5-HT 2C agonists are active in models of schedule-induced polydipsia and "differential reinforcement of low rate 72-s" in rats (Blier and De Montigny 1998;Martin et al 1998;).…”
Section: Modulation Of Frontocortical Monoaminergic Transmissionmentioning
confidence: 99%
“…Activity in this procedure is unrelated to an influence upon anxiety (benzodiazepines are inactive at non-sedative doses), but a possible relationship to compulsive behavior should be evoked, as SSRIs and clomipramine, which are potently active in this procedure (Millan et al 2001;Brocco et al 2006;Nicolas et al 2006), are clinically used for the treatment of obsessive-compulsive disorders (Erzegovesi et al 2001;Micallef and Blin 2001;Millan 2006). However, 5-HT 2C agonists are active in models of schedule-induced polydipsia and "differential reinforcement of low rate 72-s" in rats (Blier and De Montigny 1998;Martin et al 1998;).…”
Section: Modulation Of Frontocortical Monoaminergic Transmissionmentioning
confidence: 99%
“…Augmentation of SRI treatment with first-generation antipsychotics (Li et al , 2005) and certain second-generation antipsychotics (Erzegovesi et al , 2001; Fineberg and Gale, 2005) has been shown to improve therapeutic response in patients showing poor response to SRI monotherapy (Bloch et al , 2006). For example, haloperidol, risperidone, quetiapine, and olanzapine have all been shown to augment the effects of SRIs in randomized controlled trials (McDougle et al , 1994; McDougle et al , 2000; Bystritsky et al , 2004; Denys et al , 2004).…”
Section: Treatment Of Obsessive–compulsive Disordermentioning
confidence: 99%
“…Many (Zohar et al , 1987; Hollander et al , 1992; Erzegovesi et al , 2001; Gross-Isseroff et al , 2004) but not all human pharmacological challenge studies have shown that the 5-HT2B/C agonist 1-(3-chlorophenyl)piperazine (m-CPP) exacerbates symptoms in OCD patients (McDougle et al , 1995; Khanna et al , 2001; de Leeuw and Westenberg, 2008). However, m-CPP is not a highly selective 5-HT2C agonist, and shows similar IC 50 values for 5-HT2, 5-HT1A, 5-HT1B, and α2-adrenergic receptors (values ranging from 360–1300λnmol/l) (Hamik and Peroutka, 1989; Blalock et al , 2003).…”
Section: -Ht2c Knockout Micementioning
confidence: 99%
“…This compound is a nonselective serotonergic agonist that acts in the central nervous system primarily through 5HT1A/D and 5HT2C receptors . At higher doses, mCPP can also induce a general anxiogenic effect . Preclinical models of OCD indicate that mCPP treatment blocks not only the effects of the clinically effective FLX but also induces repetitive behaviors by itself .…”
Section: Introductionmentioning
confidence: 99%